Synthesis and Antifungal Screening of Some Novel Sulfur Containing Heterocyclic Compounds - DAS, BARNALI; SRIVASTAVA, SAJAL; SARVANAN, J.; MOHAN, S. (Asian Journal of Chemistry, 2010)
To a mixture of ketone (N-methyl piperidone), ethylcyano-acetate and sulfur in alcohol was added morpholine dropwise and continue the stirring until sulfur dissolves. After keeping it overnight in refrigerator, 2-amino-3-carbethoxy-6-N-methyl-4,5,6,7 tetrahydropyrido(b)thiophene (I) resulted out. The compound I was then reacted with carbon disulphide, NaOH, dimethyl sulphate in dimethyl sulphoxide under cold condition to form compound II. This was refluxed with hydrazine hydrate in isopropanol as a solvent to get the cyclized compound III. Finally, the compound III was reacted with substituted aryl aldehydes to yield a total of nine new Schiff bases. Of the nine Schiff bases screened for antifungal activity the compounds JSB 7 and JSB 8 was found to exhibit goodantifungal activity.